Penerapan Algoritma Naive Bayes Untuk Memprediksi Jumlah Produksi Barang Berdasarkan Data Persediaan dan Jumlah Pemesanan pada Cv. Papadan Mama Pastries - Effrida Manalu; Fricles Ariwisanto Sianturi; Mamed Rofendy Manalu (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2017)
CV. Papa and Mama is a company engaged in the field of baking and bread making industry and marketing the products to various places. CV. Papa and Mama Pastries have difficulty managing data on bread supplies and bread order receipts that are often overproduced and lacking in production due to inaccurate data. To support an effective bread supply it is necessary to design a system based on Visual Basic 2010 that can solve the problem. The authors apply the Naive Bayes method to provide a solution in predicting bread inventory and bread order acceptance taken based on data last year. Thus, it can help in determining the stock of bread stock in accordance with the needs and desires and produce an alternative choice of bread stock.Keywords : Prediction, Bread Stock, Naive Bayes Method.